Pengaruh Mental Toughness dan Employee Experience Terhadap Organizational Commitment Dengan Psychological Well-Being Sebagai Mediator Pada Karyawan Generasi Z di Jakarta - Fitrinita Rumindang Simanjuntak; Netania Emilisa; Tiara Puspa (Jurnal Ilmiah Ekonomi Global Masa Kini, 2023)
Organizational commitment is an important factor for companies in improving their productivity and performance. However, there are stereotypes related to the commitment of Generation Z employees who are new to the workplace, namely, a tendency to be disloyal and a low commitment to the organization. The study aims to analyse the impact of Mental Toughness and Employee Experience on Organizational Commitment with Psychological Well-Being as Mediator on Generation Z Employees in Jakarta. Generation Z is the generation of professionals born between 1997 and 2005 who have recently entered the world of work.  This research uses analytical techniques with quantitative methods with a survey approach. A sample of 125 Generation Z employees at a start-up company in Jakarta. The research data was collected using a Likert-scale questionnaire that had 25 statement items that included four variables: mental toughness, employee experience, psychological well-being, and organizational commitment. Hypothesis testing uses SEM (Structural Equation Modelling) as well as SPSS and AMOS software to process data. The results of the study show that Mental toughness has a positive influence on Psychological well-being, Employee experience has a positively influenced psychological wellness, Psychological wellness has a negative influence upon Organizational commitment, and Psychological welfare has a mediating influence between mental toughness and Organizational engagement and the absence of Psychological Well-Being as a mediation between employee experience and Organizational commitment.